Development of Interactive Multimedia in Manicure and Pedicure Learning to Improve Students’ Understanding - Siti Nadyatul Choeriyah; Anik Maghfiroh; Ade Novi Nurul Ihsani; Trisnani Widowati (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
The main problem in manicure and pedicure learning at SMK Negeri 6 Semarang is the limited availability of interactive learning media, which causes students difficulties in understanding practical materials. This study aimed to develop Google Sites-based interactive multimedia learning media and to examine its feasibility and effectiveness in improving students’ understanding. The research employed a Research and Development (R&D) method using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The participants consisted of 30 tenth-grade students from the Beauty Department of SMK Negeri 6 Semarang. Data were collected through expert validation sheets and student learning outcome tests. Media feasibility was analyzed using percentage techniques, while effectiveness was examined through N-gain and paired sample t-tests. The findings revealed that the developed media achieved a very high feasibility level, with scores of 96.88% from material experts and 90.20% from media experts. The effectiveness of the media was indicated by the improvement in students’ average learning outcomes from 61 in the pre-test to 86.5 in the post-test, with an N-gain score of 0.654 categorized as moderate. The paired sample t-test showed a p-value < 0.001, indicating a significant difference between pre-test and post-test results. These findings demonstrate that the Google Sites-based interactive multimedia learning media is feasible and effective for manicure and pedicure learning.